The role of complementary learning systems in learning and consolidation in a quasi-regular domain. (July 2019) - Mirković, Jelena; Vinals, Lydia; Gaskell, M.G.
Abstract: We examine the role of off-line memory consolidation processes in the learning and retention of a new quasi-regular linguistic system similar to the English past tense. Quasi-regular systems are characterized by a dominance of systematic, regular forms (e.g., walk-walked, jump-jumped) alongside a smaller number of high frequency irregulars (e.g., sit-sat, go-went), and are found across many cognitive domains, from spelling-sound mappings to inflectional morphology to semantic cognition. Participants were trained on the novel morphological system using an artificial language paradigm, and then tested after different delays. Based on a complementary systems account of memory, we predicted that irregular forms would show stronger off-line changes due to consolidation processes. Across two experiments, participants were tested either immediately after learning, 12 h later with or without sleep, or 24 h later. Testing involved generalization of the morphological patterns to previously unseen words (both experiments) as well as recall of the trained words (Experiment 2). In generalization, participants showed 'default' regularization across a range of novel forms, as well as irregularization for previously unseen items that were similar to unique high-frequency irregular trained forms. Both patterns of performance remained stable across the delays. Generalizations involving competing tendencies to regularize and irregularize were balanced between the two immediately after learning. Crucially, at both 12-h delays the tendency to irregularize in these cases was strengthened, with further strengthening after 24 h. Consolidated knowledge of both regular and irregular trained items contributed significantly to generalization performance, with evidence of strengthening of irregular forms and weakening of regular forms. We interpret these findings in the context of a complementary systems model, and discuss how maintenance, strengthening, and forgetting of the new memories across sleep and wake can play a role in acquiring quasi-regular systems.